To evaluate the accuracy of various dental parameters used for the gender determination in Nagpur District population - Swapnil N Patil; Sushil B Naik; Seema D Kamble; Vandana B Kokane (Wolters Kluwer Medknow Publications, 2015)
Context: Gender determination is considered an important step in reconstructing the biological profile of unknown individuals from the forensic context. Assessment of sex differences from human remains will be of immense help as it would narrow down fields of search to 50 %. Aims: To evaluate the accuracy of various dental parameters used for the gender determination. Settings and Design: The aim of the present study was to investigate the accuracy of various methods employed in gender determination or personal identification such as mesiodistal width of molars, mesiodistal width of canine, mandibular and maxillary canine index in age group of 15 to 65 years. Methods and Material: A total of 200 patients were selected comprising of both the genders in the age group of 15-65 years belonging to various parts of Nagpur. The mesiodistal crown width of mandibular and maxillary permanent molar and canine teeth and the intercanine distance was measured and the values were noted. Statistical analysis used: the data was analysed using SPSS 18 software. Results: The mean of mesio distal width of maxillary and mandibular molar in males and females is suggestive of gender dimorphism in maxillary molars which was statistically significant.The maxillary inter-canine distance was greater in males and was statistically significant. Conclusions: The dental parameters can be used as a tool for accurate gender determination in forensic investigations.